PENERAPAN METODE QIRA’ATI DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN ANAK-ANAK TPA DI DESA POKO - Dwinata, Danti; Ayuningrum, Tyas; Batutah, Muhammad Ibnu Ronggo; Khoirurrosyidin, Khoirurrosyidin (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2025)
This study aims to describe the application of the Qira'ati method in improving the quality of children's reading of the Qur'an at the Al-Qur'an Education Park (TPA) in Poko Village, Jambon District, Ponorogo Regency. The background of this study is that many children still experience difficulties in pronouncing Hijaiyah letters, applying tajwid rules, and reading fluently and clearly. This study uses a descriptive qualitative approach with children and teachers at the TPA in Poko Village as subjects. Data collection techniques include direct observation of the learning process, interviews, documentation of administration and photos of activities, as well as Qur'an recitation tests before and after the application of the method. The results of the study show that the Qira'ati method successfully improves the children's fluency, accuracy of makhraj, application of tajwid rules, and regularity of rhythm (tartil). Each child can move up a level gradually after mastering the previous stage, so that the learning process becomes structured and motivating, and builds the children's self-confidence. In addition to technical aspects, this method also fosters discipline, motivation, and a spirit of healthy competition among children. The obstacles identified include the limited number of teachers compared to the number of children and differences in children's learning abilities. Overall, the Qira'ati method has proven to be systematic, relevant, and effective in improving the quality of Al-Qur'an recitation and fostering the religious character of children at the Poko Village TPA.